A de novo frameshift variant of ANKRD11 (c.1366_1367dup) in a Chinese patient with KBG syndrome - Jing Chen; Zhongmin Xia; Yulin Zhou; Xiaomin Ma; Xudong Wang; Qiwei Guo (BMC, 2021)
Abstract Background KBG syndrome is a rare autosomal dominant genetic disease mainly caused by pathogenic variants of ankyrin repeat domain-containing protein 11 (ANKRD11) or deletions involving ANKRD11. Herein, we report a novel de novo heterozygous frameshift ANKRD11 variant via whole exome sequencing in a Chinese girl with KBG syndrome. Case presentation A 2-year-2-month-old girl presented with a short stature and developmental delay. Comprehensive physical examinations, endocrine laboratory tests and imaging examination were performed. Whole‐exome sequencing and Sanger sequencing were used to detect and confirm the variant associated with KBG in this patient, respectively. The pathogenicity of the variant was further predicted by several in silico prediction tools. The patient was diagnosed as KBG syndrome with a short stature and developmental delay, as well as characteristic craniofacial abnormalities, including a triangular face, long philtrum, wide eyebrows, a broad nasal bridge, prominent and protruding ears, macrodontia of the upper central incisors, dental crowding, and binocular refractive error. Her skeletal anomalies included brachydactyly, fifth finger clinodactyly, and left-skewed caudal vertebrae. Electroencephalographic results generally showed normal background activity with sporadic spikes and slow wave complexes, as well as multiple spikes and slow wave complexes in the bilateral parietal, occipital, and posterior temporal regions during non-rapid-eye-movement sleep. Brain MRI showed a distended change in the bilateral ventricles and third ventricle, as well as malformation of the sixth ventricle. Whole exome sequencing revealed a novel heterozygous frameshift variant in the patient, ANKRD11 c.1366_1367dup, which was predicted to be pathogenic through in silico analysis. The patient had received physical therapy since 4 months of age, and improvement of gross motor dysfunction was evident. Conclusions The results of this study expand the spectrum of ANKRD11 variants in KBG patients and provide clinical phenotypic data for KBG syndrome at an early age. Our study also demonstrates that whole exome sequencing is an effective method for the diagnosis of rare genetic disorders.